Histological Pattern of Bronchial Carcinoma in Tertiary Care Hospital in Bangladesh - Podder, Mousumi; Mahejabin, Farzana; Razzaque, SM Abdur; Farah, Shayela; Roy, Manoranjan; Podder, Gourab (Chest & Heart Journal, 2023)
Background: Lung cancer is the most common malignant neoplasm worldwide. Among all human cancers, carcinoma of the lung has the highest mortality rate and is the leading cause of all cancer deaths. However, histological types may vary with the changes in geographical region, smoking status and other social factors. Among the few published reports, squamous cell carcinoma of lung is more common in male smokers. Aim: This study was aimed to find out the specific histological type of lung cancers patients of Bangladeshi people. Methods: This was a cross-sectional study and was conducted on bronchial carcinoma patients who had been admitted and diagnosed at the department of respiratory medicine, National Institute of the diseases of the Chest & Hospital (NIDCH). Total 120 diagnosed case of bronchial carcinoma were included in the study. The respondents were divided into two groups, smokers and non-smokers.Following informed written consent, 100 smoker and 20 non-smoker patients were interviewed and information was recorded in the questionnaire. The laboratoryinvestigations were collected from patients or attendants. Ethical issues were maintained and the results of histological diagnosis were obtained to complete the data sheet and analyzed by SPSS, Z test, t test, chi-square test. Results: A total of 120 patients were interviewed. Among them, 86.7% were males and 13.3% were females and ratio were 6.5:1. The mean age of the patients were 59.41±2.89 years.Out of the 120 patients, 100 patients (83.3%) had history of smoking in their life time and 20 patients (16.7%) were non-smoker. In case of male, majority of patients were smokers (82.5%) and in case of female, majority of patients (12.5%) were non -smokers. Among smokers, squamous cell carcinoma (44.1%) was the most common histological type followed by adenocarcinoma (6.7%). In case of non -smokers, the status was entirely different and here adenocarcinoma was the most common type and which constituted 11.7% and squamous cell carcinoma in nonsmokers was less and only 1.7%. Among male patients 45% had squamous cell carcinoma which was higher than other histological types of cancer. In case of female patients 10.83% had adenocarcinoma, which was higher than other histological types of lung cancer. Conclusion: In male smokers, squamous cell carcinoma is still the most frequent histological type of bronchial carcinoma in present study. In case of females and non-smokers adenocarcinoma is the predominant histological type. Chest Heart J. 2021; 45(1) : 12-18